2022
DOI: 10.1371/journal.pone.0274123
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adsorption of some heavy metals using extracted chitosan anchored with new aldehyde to form a schiff base

Abstract: A new aldehyde 2,2’-[propane-1,3-diylbis(oxy)] dibenzaldehyde was synthesized from refluxing 2-hydroxy acetophenone and 2-hydroxy 1,3-dichloropropanean in an alcoholic medium. The compositions and properties of the new aldehyde compound were characterized by elemental analysis, FTIR, and nuclear magnetic resonance spectroscopy studies. The extracted chitosan was made to react with a new aldehyde to form a Schiff base by a suitable method. The effects of initial concentration of metal ions, exposure time, imine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The SF values for the three metal ions on SBL at metal ion concentrations of 1 mg/L and 2000 mg/L were studied and are presented in Tables 3; Table 4 for water and soil samples, respectively. The SF values were less than unity for all the metal ions from both samples, demonstrating the favorable potential of the sorbent SBL for the selected metal ions uptake; similar findings were observed in other studies (Sharef and Fakhre, 2022).…”
Section: Adsorption Isotherms Study For Aqueous and Soil Samplessupporting
confidence: 89%
See 1 more Smart Citation
“…The SF values for the three metal ions on SBL at metal ion concentrations of 1 mg/L and 2000 mg/L were studied and are presented in Tables 3; Table 4 for water and soil samples, respectively. The SF values were less than unity for all the metal ions from both samples, demonstrating the favorable potential of the sorbent SBL for the selected metal ions uptake; similar findings were observed in other studies (Sharef and Fakhre, 2022).…”
Section: Adsorption Isotherms Study For Aqueous and Soil Samplessupporting
confidence: 89%
“…It can also be seen that the increased quantity of SBL from 0.1 g did not significantly influence the sorption percentage. This could be associated with the excess amount of the sorbent preventing the metallic cations from approaching the active sites of the adsorbent (Sharef and Fakhre, 2022).…”
Section: Adsorbent Dosage Effects On Removal Efficiencymentioning
confidence: 99%
“…The original Fe-BC had more phenolic hydroxyl groups forming an intermolecular hydrogen bond than La-BC, but the crosslinking (relative to amino groups) density was lower. FTIR spectra showed that the modified BC chain was grafted onto the modified BC chain through a Schiff base reaction 42 and the modified BC chain was developed into a three-dimensional network through hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it showed a signal for the hydroxyl group at 8.01-10.09 ppm, whereas the methylene proton was represented by 4.40 ppm. CHaliphatic protons were referred to as a quintet at 4.71 ppm [24].…”
Section: H-nmr Spectrummentioning
confidence: 99%